Semi-in-situ cutting force measurement of a jigsaw - Sándor Apáti; György Hegedűs; Sándor Hajdu (Results in Engineering)
This article presents a measuring method to measure the cutting force of a jigsaw without taking it apart or making any changes to it. The primary objective was to design a measuring process and method that does not require disassembly or modification of the saw. A measurement rig was designed to securely mount the saw, the load cell, and the inductive sensors needed for speed measurements, making it possible to measure cutting forces accurately under different working conditions. The method uses Fast Fourier Transform (FFT) analysis to determine the motor speeds, which helps calculate dynamic cutting parameters correctly. The study shows how feed rates, crank speeds, and material properties affect cutting forces. It also shows that higher speeds usually make the tool more efficient but can cause problems if too high. Tests on materials like acacia wood, aluminum alloy (AlMgSi1), and methamid (P6) showed significant differences in how they cut because of their density and homogeneity. The results show that the forces needed to cut materials depend on the size of the chip being removed, and this is important for making tools last longer and cutting more accurately. The study also found unusual patterns, like sudden force spikes or negative values, due to the material inhomogeneity and the spring back of the sawing blades. The method of measuring forces without disassembling the jigsaw power tools can be used for cutting wood, plastic, and metal, and it helps improve industrial cutting tools. The findings highlight the importance of more research to understand better how forces change during cutting, improve cutting settings, make tools last longer, use less energy, and improve the quality of the finished material. This research helps advance cutting technology for woodworking and precision machining.